Katedra za šport na univerzi med letom 1971 in 2018 - Filipič-Jeras, Ksenija (Šport (Ljubljana), 2019)
Sports pedagogues employed at the members of UL have been merging and working between 1971 and 2017 at the Department of Sport at the University of the Faculty of Sport. Department was fundamental organizational unit where knowledge and experience flew into theory and practice. Guidelines of university sport is a document that has been shaped in time with some updates that designed the foundations of university sport activities until the beginning of the introduction of Bologna students programs. The development of a strategy for development of sports activities of students at the University analytically processed and indicated the direction completed by the members of the Department of Sport at the University with proposed hierarchical model of the organization of sport at the University of Ljubljana and in the wider Slovenian university space. Since March 2019, sports educators have been active in the Group of sports pedagogues at the UL members.
Keywords: group; guidelines; Katedra za šport; organised; organiziranost; skupina; smernice; sport; strategija; strategy; šport; University of Ljubljana; university sport; University Sports Department; Univerza v Ljubljani; univerzitetni šport